(untitled) (Global Journal of Management and Business Research, 2022)
The purpose of this study is to understand how the work-family conflict contributes to the lack of involvement of employees in Cameroonian SMEs and the means to be implemented to allow a good involvement of employees in this category of companies in Cameroon. We conducted exploratory qualitative research with a sample of employees working in Cameroonian SMEs. The results of our analyses have thus led to the conclusion that the work-family conflict contributes to the lack of involvement of employees within companies (SMEs). That is to say, the difficulty of reconciling the two spheres (family and work) by employees influences the normative, calculated, and affective involvement in work.